A Global Diet Quality Index and Risk of Type 2 Diabetes in U.S. Women. (29th May 2020) - Fung, Teresa; Bromage, Sabri; Li, Yanping; Bhupathiraju, Shilpa; Batis, Carolina; Fawzi, Wafaie; Holmes, Michelle; Stampfer, Meir; Hu, Frank; Willett, Walter
Abstract: Objectives: No tool to measure diet quality on the global scale currently exist. At the same time, type 2 diabetes is a global issue for women, including those under age 50. As part of an effort to develop an instrument to assess diet quality, this analysis the ability of a global diet quality score to predict type 2 diabetes in women in a high-income country. Therefore, the objective of this analysis is to examine prospectively the association between the Global Diet Quality Score (GDQS) and risk of type 2 diabetes, and potential differences in association by age, among U.S. women. Methods: Health, lifestyle, and diet information was collected from women ( n = 88, 520) in the Nurses' Health Study II through repeated questionnaires between 1991 and 2017. The GDQS consisted of 25 food groups and points were awarded for higher intake of healthy groups and lower intake of unhealthy groups (maximum of 49 points). Multivariable hazard ratios (HR) were computed for confirmed type 2 diabetes using Cox proportional hazards models. Results: We ascertained 6319 incident type 2 diabetes during follow-up. The multivariable HR comparing top to bottom quintile of GDQS was 0.83 (95% CI = 0.76–0.91, p trend < 0.001). The association for women under age 50 was 0.77 (0.68–0.88, p trend < 0.001) and for age 50+ was 0.69 (0.52–0.93, p trend < 0.001) with no significant interaction. Analysis of the healthy and unhealthy subscores of the GDQS showed an inverse association with lower intake of unhealthy components (HR comparing top to bottom quintile of the unhealthy subscore = 0.69, 95% CI = 0.62–0.77, p trend < 0.001) but not higher intake of healthy components. The inverse association for each 1-SD increase in the GDQS (HR = 0.93, CI = 0.91–0.96) was stronger ( P < 0.001) than the Minimum Diet Diversity score for Women (MDDW) (HR = 1.00, CI = 0.94–1.04) but slightly weaker ( P = 0.03) than the Alternate Healthy Eating Index-2010 (AHEI-2010) (HR = 0.91, CI = 0.88–0.94). Conclusions: A higher GDQS was inversely associated with type 2 diabetes risk in U.S. women, mainly due to lower intake of unhealthy foods. The association did not appear to differ by age. The GDQS performed nearly as well as the AHEI-2010. Funding Sources: Funding for this work was provided by Intake - Center for Dietary Assessment at FHI Solutions.